Exploring the Effect of Team-Environment Fit in the Relationship Between Team Personality, Job Satisfaction, and Performance - Lin, Xin; Sivarak, Ornlatcha; Chou, Tung-Hsiang; Lin, Yu-Ting; Rahardja, Untung; Ruangkanjanases, Athapol; Lin, Yu-Chun; Chen, Shih-Chih (Frontiers in Public Health, 2022)
This study explores whether team-organization fit (T-O fit) and team-job fit (T-J fit) play a mediating role between team personality, team job satisfaction, and team performance. Conscientiousness and openness to experience are common antecedents of team personality. Additionally, T-O fit and T-J fit are derived from person-environment fit theory, which is used to discuss the interaction between team members and the environment that affects behavior. The research purpose is to understand the factors that affect job satisfaction and performance from a team perspective. This is different from previous studies based on an individual perspective. The research object of this study has 365 respondents from 81 teams in different industries, and the structural equation modeling is applied to the empirical analysis. The research results show that T-J fit has a significant mediating effect on team personality and team job satisfaction. The team job satisfaction has also a significant mediating effect on team personality and team performance. Therefore, when team members recognize their work, they work harder to achieve team job satisfaction and performance. This study suggests that companies not only pay attention to the work abilities of employees, but also understand the fit between them and their jobs.